Review of Sound Sculpture: A Collection of Essays by Artists Surveying the Techniques; Applications; and Future Directions of Sound Sculpture, Ed. John Grayson, Environments of Musical Sculpture You Can Build: Phase 1 by John Grayson, and Biofeedback and - Orton, Richard (Contact: A Journal for Contemporary Music (1971-1990), 1976)